Development of an Augmented Reality-Based E-Learning Module to Enhance Vocational Students’ Collaborative and Communication Skills - Isnaini Wulandari; Widiyanti; Syarif Suhartadi (STAI Miftahul Ula Nganjuk, 2025)
This study aims to develop an Augmented Reality (AR)-based e-learning module intended to enhance vocational students’ collaborative and communication skills. The study addresses the limited availability of interactive and engaging digital learning media that effectively support the development of 21st-century skills. The research adopted a Research and Development (R&D) approach utilizing the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires, observations, and interviews, and analyzed using both qualitative and quantitative methods. The product was validated by media and material experts, yielding an average score of 93,5%, categorized as very Valid. The results indicate that the developed AR-based e-learning module is effective in improving students’ collaboration and communication skills and can serve as an innovative digital learning medium in vocational education.